If You Give a Moose a Muffin - Numeroff, Laura Joffe; Bond, Felicia ([New York] HarperCollins Publishers, 1991)
Chaos can ensue if you give a moose a muffin and start him on a cycle of urgent requests.
Keywords: Moose -- Fiction; Humorous stories